2020
DOI: 10.1097/md.0000000000020409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi on psychological disorder in college students

Abstract: Background: This study will explore the effect of Tai Chi on psychological disorder (PD) in college students (CS). Methods: A comprehensive literature search of relevant randomized controlled trials will be carried out in electronic databases from inception to the February 29, 2020: PUBMED, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure. There are not limitations related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…e unique function of running APP attracts the attention of college students, so that they can cultivate their correct exercise habits [1]. Jiang et al's survey of college students shows that 89.3% of boys like physical exercise, 68.1% of girls like physical exercise, and 10.7% of boys feel below average; girls accounted for 30.6%, which shows that girls' interest in physical exercise is slightly worse than that of boys [2]. Liu et al pointed out that most students hold a good attitude toward exercise, but according to grades, the scores of exercise attitude vary from grade to grade, and the scores of lower grades are generally better than those of higher grades [3].…”
Section: Introductionmentioning
confidence: 99%
“…e unique function of running APP attracts the attention of college students, so that they can cultivate their correct exercise habits [1]. Jiang et al's survey of college students shows that 89.3% of boys like physical exercise, 68.1% of girls like physical exercise, and 10.7% of boys feel below average; girls accounted for 30.6%, which shows that girls' interest in physical exercise is slightly worse than that of boys [2]. Liu et al pointed out that most students hold a good attitude toward exercise, but according to grades, the scores of exercise attitude vary from grade to grade, and the scores of lower grades are generally better than those of higher grades [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies concluded that mind-body therapies, such as yoga and qigong, effectively improved negative psychological aspects, such as anxiety and depression, in college students. 17 , 18 However, most current studies only compared two to two for efficacy analysis, and few evidence-based studies compared the effectiveness of multiple MBEs in improving depression and anxiety symptoms simultaneously. A review by Larun et al.…”
Section: Introductionmentioning
confidence: 99%